Pelaksanaan Humas pada Pendidikan Agama Islam dalam Meningkatkan Mutu Sekolah di Madrasah - Setiawan, Farid; Fadli, Nafis Abqori; Ananda, Alfina Duta; Agustin, Dhani Fernandia; Febriani, Anisa Nur (MASALIQ, 2022)
The purpose of this study was to find out how the implementation of public relations in Islamic religious education in improving the quality of schools in madrasas. The research method used uses library research methods from book sources and journal articles that are relevant to the topics raised in this article. Public relations in schools or madrasas is an important part that has a role to provide information related to education to improve harmonious relationships effectively and efficiently with the community. The role of public relations is very influential in improving the quality of schools or madrasas, especially to increase community participation to take part in education in schools. For this reason, it is necessary to have quality and quality public relations management to achieve educational goals. In its implementation, the relationship between the community and the school has a mutually beneficial reciprocity, where the school is a place to seek knowledge and the community is a place to apply the knowledge that has been obtained, there are also obstacles experienced in implementing public relations management with the community, namely there has not been effective communication between public relations. with DU/DI and their parents, and also the lack of human resources who study this field of public relations